Burn wound dressing using honey hydrogel versus hydrogel - Amnah, Ab Halim (Universiti Sains Malaysia, 2006)
Burn injury results in either the loss or disruption of skin functions. Skin plays its main roles in protection, immunological, homeostatsis and thermoregulation, neurosensory, etc .. Honey is believed to be the best ancient medicine to cover wounds that causes by burn either thermally or electrically. The unique ingredients of honey acts by inhibiting gram positive and negative bacteria, promotes epithelialization and burn healing. This project is to assess the impact of honey on wound dressing for burn wound treatment. The study compared the effectiveness of honey hydrogel in bum wound healing with hydrogel agar as a control. Burn wounding rats were chosen as the study model. Twelve female Sprague-Dawley rats were divided into two equal of size n=6 and kept in same room with same food and environment. The operation was done under aseptic technique, in sterile condition. At first, rats were anaesthetized with ketamine injection and disinfectant with alcohol and povidone iodine. Burn lesion was created by applying hot metal plate for ten seconds on the back of the rats. The first group was treated by honey hydrogel while the other group was covered by hydrogel agar only. Honey hydrogel is actually a hydrogel whereby 6% of the water content replaced with honey. They were supervised daily and on the 7th and 14th day postoperatively the burn lesion was measured. The average of burn wound size on day 14 for honey hydrogel and hydrogel was 0.24 em 2 and 0.64 em 2 respectively. This indicates that wound treated with honey hydrogel contracts faster and seem to be more effective than hydrogel as it provides moist and good bedding for epithelialisation that can heals the faster.